Defining familiarity in nursing homes providing care for residents with dementia: a scoping review - Sun, Joanna; Brennan, Sumiyo; Doan, Therese (Frontiers in Dementia, 2025)
ObjectiveThis study explores the underpinning definitions associated with familiarity in the context of dementia inclusive design and nursing home environment.BackgroundEnvironmental design in nursing homes impacts the quality of life and care of residents with dementia. One of the key principles of design is the need for the environment to achieve a sense of familiarity. However, there are divergent perspectives regarding the term “familiarity.” Inconsistent definitions are challenging to understand, and they continue to impact the implementation of good design. To that end, this scoping review examines the definitions and associated with familiarity, dementia, and the design of nursing home environments.MethodsThe Arksey and O'Malley methodological framework and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews ensure the rigor of the scoping review. Searches were conducted using six databases for peer-reviewed publications in English from 1991 to 2023. Search terms included “dementia,” “nursing home,” “long-term care,” “familiar,” “familiarity,” and “environments.”ResultsThe searches yielded 245 publications. Of those, 46 studies from 19 countries were included in this review. The review uncovered three central themes and compelling evidence citing the inclusion of homelike environments. Emphasis on design considerations includes the wellbeing of the designated population and the need to embrace multisensory integration in the design process.ConclusionsA strong link exists between familiarity and key design considerations, such as a homelike environment, wellbeing, and multisensory integration. These considerations can enhance the effectiveness of the design of familiar environments.